Midwives Readiness Factors in Maintaining Patient Confidentiality in the Digital Medical Record Era - Rahayu, Ayu Hendrati; Marlina, Lusi; Rochmawati, Rochmawati (Jurnal Kesehatan Vokasional, 2025)
Background: The digitalization of medical records in healthcare systems created new challenges in maintaining patient information confidentiality, particularly in midwifery practice. The transition from manual to electronic systems required midwives' readiness to understand and implement confidentiality ethics in accordance with digital technology developments.Objective: This research aimed to analyze the factors that influence midwives' readiness in upholding patient confidentiality ethics in the era of medical record digitalization.Methods: The research employed a cross-sectional design with a sample of 150 midwives. Data collection was conducted through structured questionnaires measuring variables of data protection regulation knowledge, digital competence, confidentiality ethics knowledge, and attitudes toward digitalization. Data were analyzed using multiple regression.Results: Regression analysis showed the research model explained 52.9% of variation in midwives' readiness to uphold confidentiality ethics. Three variables had significant influence: knowledge of data protection regulations (coefficient=0.316; p=0.001), digital competence (coefficient=0.131; p=0.001), and knowledge of confidentiality ethics (coefficient=0.084; p=0.027). Attitude toward digitalization did not have a significant effect.Conclusion: Midwives' readiness in upholding patient confidentiality ethics in the digital era was influenced by mastery of data protection regulations, digital competence, and understanding of confidentiality ethics. This research was beneficial for developing strategies to enhance midwives' competencies in facing healthcare system digitalization.